The TOE Theory Perspective on the Adoption of Accounting Information Systems: The Role of Innovative Leadership as a Catalyst for Public Sector Digitalization - Gita Panji Sasmita; Imaniar Septiani Rais; Intan Nita Isbach; Hariyati; Eni Wuryani (International Journal Of Economics Social And Technology, 2026)
While the Technology-Organization-Environment (TOE) framework is widely used to understand how organizations adopt new technologies. However, its relevance in the public sector where digitalization is often a mandatory compliance rather than a voluntary choice remains underexplored. This study bridges that gap by investigating how Technological Capital, Organizational Culture, and Environmental Uncertainty drive the adoption of Accounting Information Systems (AIS), specifically the Local Government Information System (SIPD). Additionally, we examine whether Innovative Leadership acts as a catalyst in this process. Using a quantitative explanatory design, we surveyed 187 civil servants operating the SIPD in the Rembang and Madiun Regencies. The SEM-PLS analysis reveals a compelling dynamic: Technological Capital and Environmental Uncertainty significantly propel AIS adoption, whereas Organizational Culture shows no meaningful impact. Interestingly, Innovative Leadership effectively strengthens the role of Technological Capital but does not moderate the organizational and environmental factors. These findings offer a fresh theoretical perspective on the TOE framework, suggesting that in heavily regulated government settings, tangible infrastructure and external regulatory pressures simply override internal cultural readiness. For local governments, this underscores a clear practical directive: accelerating digital transformation requires prioritizing concrete technological investments and positioning digitally competent leaders, rather than relying solely on cultural shifts.